PERAN EDUKATIF DAN KONSULTATIF PENYULUH AGAMA ISLAM DALAM PENURUNAN TINGKAT KRIMINALITAS DAN PENCIPTAAN KEHARMONISAN MASYARAKAT DI LAMPUNG TIMUR - Uswatun Hasanah; Nurul Fadilah (Pascasarjana IAIN Sultan Amai Gorontalo, 2022)
Diversity and differences in ethnicity, culture and religion, apart from being the heritage of the Indonesian nation, also have an impact on the emergence of conflicts and criminal acts. However, in several areas, including in East Lampung, there has cc/ been a decrease in crime in the last four years, which is believed to be influenced by the role of Islamic religious counselor. This study aims to examine the educative and consultative role of Islamic religious counselor in crime-prone area for community harmony in East Lampung. This study used a qualitative method using a case study design. The research participants are all of islamic counselors who worked in Office of Religious Affairs (KUA) in several areas prone to criminal in the East Lampung such as Jabung, Labuhan Maringgai, and Gunung Pelindung. These areas were chosen pusposively based on the highest crime rate areas in East Lampung. Research results show that participation Islamic religion counselor can effectively improve the character of society, especially the mother and the father in a family with optimizing various religious activities so that potential criminal action will be minimized. Islamic counselors are found to have a better approach in educating the society rather than teacher, and able to give in-dept counceling than general counselor because they basically understand more on the ciscumstances and condition in those societies. In addition, the collaboration and synergy between islamic counselor, the government, and the community can optimize any effort to create a harmonious, safe, and prosperous society.